Effects of cognitive stimulation on neuropsychiatric symptoms in elderly with Alzheimer's disease: A systematic review - Fukushima, Raiana Lídice Mór; Carmo, Elisangela Gisele Do; Pedroso, Renata Do Valle; Micali, Pollyanna Natalia; Donadelli, Paula Secomandi; Fuzaro Junior, Gilson; Venancio, Reisa Cristiane De Paula; Viola, Juliana; Costa, José Luiz Riani (Associação de Neurologia Cognitiva e do Comportamento, 2016)
ABSTRACTIntroduction:Neuropsychiatric symptoms are frequent in Alzheimer's disease and negatively affect patient quality of life.Objective:To assess the effectiveness of cognitive stimulation on neuropsychiatric symptoms in elderly patients with Alzheimer's disease.Methods:The included articles were reviewed between December 2015 and June 2016, and the inclusion criteria were: (1) studies involving older adults diagnosed with Alzheimer's disease; (2) studies published in English, Spanish or Portuguese; (3) studies that determined the effect of cognitive stimulation on neuropsychiatric symptoms in elderly patients with Alzheimer's disease; (4) controlled trials.Results:Out of the total 722, 9 articles matched the inclusion criteria. Depression, apathy and anxiety were the most frequent symptoms.Conclusion:Studies reported significant results post-treatment, suggesting cognitive stimulation can be effective for these neuropsychiatric symptoms, thus improving the quality of life of Alzheimer's disease patients and their caregivers.

RESUMOIntrodução:Sintomas neuropsiquiátricos são frequentes na doença de Alzheimer e afetam negativamente a qualidade de vida destes pacientes.Objetivo:Avaliação da eficácia da estimulação cognitiva sobre os sintomas neuropsiquiátricos em idosos com doença de Alzheimer.Métodos:Os artigos incluídos foram revisados no período de Dezembro (2015) à Junho (2016) e os critérios de inclusão foram: (1) estudos com idosos com diagnóstico de doença de Alzheimer; (2) estudos publicados em Inglês, Espanhol e Português; (3) estudos que verificaram o efeito da estimulação cognitiva nos sintomas neuropsiquiátricos em idosos com doença de Alzheimer; (4) ensaios controlados.Resultados:Do total de 722, 9 artigos corresponderam aos critérios de inclusão. Depressão, apatia e ansiedade foram os distúrbios mais frequentes.Conclusão:Após tratamento, estudos relataram resultados significativos, o que sugere que a estimulação cognitiva pode ser eficaz nestes sintomas neuropsiquiátricos, melhorando assim, a qualidade de vida de pacientes com doença de Alzheimer, bem como, de seus cuidadores.
Efeitos da estimulação cognitiva nos sintomas neuropsiquiátricos em idosos com doença de Alzheimer: uma revisão sistemática
Keywords: Alzheimer's disease; depression; apathy; anxiety; dementia; cognitive stimulation; doença de Alzheimer; depressão; apatia; ansiedade; demência; estimulação cognitiva